Cultural diversity in neuropsychological assessment developing understanding through global case studies - Irani, Farzin (Routledge, 2022)
"Cultural Diversity in Neuropsychological Assessment provides a platform for clinical neuropsychologists, psychologists, and trainees to bridge cultures and speak to each other about the ethnically diverse communities they serve throughout the world. It allows readers to peek into their clinical filing cabinets and examine how they worked with diverse individuals from indigenous and migrant communities of Arab, Asian, European, Israeli, Latin American and Caribbean, Persian, Russian, Sub-Saharan African, and North American origin. The book first reviews important foundations for working with diverse communities that include key knowledge, awareness, skills, and action orientation. It then provides a collection of cases for each cultural geographic region. Each section begins with an introductory chapter to provide a bird's eye view of the historical and current state of clinical and research practice of neuropsychology in that region. Then, each chapter in the handbook focuses on a specific community by providing surface and deep level cultural background knowledge from the authors' unique perspectives. A case study is then covered in depth to practically showcase an evaluation with someone from that community which is followed by a summary of key strategic points, lessons learned, references, further readings, and a glossary of culture specific terminology used throughout the chapter. In the end, the appendix provides a list of culturally relevant tests and norms for some communities. This ground-breaking peer-reviewed handbook provides an invaluable clinical resource for neuropsychologists, psychologists, and trainees. It increases self-reflection about multicultural awareness and knowledge, highlights practical ways to provide culturally aware neuropsychological and psychological assessments, and sparks further discussion for professional and personal growth in this area"-- Provided by publisher.